DOES MULTILINGUALISM ENDANGER LEARNERS’ IDENTITY? A NARRATIVE CASE STUDY OF ENGLISH EDUCATION PROGRAM STUDENTS - Astuti, Risa; Nurjamin, Lucky Rahayu; Hamzah , Amir (English Education and Applied Linguistics Journal (EEAL Journal), 2024)
The phenomena of multilingualism influence how an individual constructs their identity, as language is one aspect of who they are. This study aims to investigate how five English college students view multilingualism and how it affects their sense of self. Semi-structured interviews were used as an instrument to collect the data, and it was found that their loyalty towards the local and national languages remains strong despite their exposure to the use of EFL in their daily lives. As multilingual speakers, the participants know the importance of maintaining their native language as their identity marker. Nonetheless, they agreed that being exposed to English changed their self-concept. These results demonstrate that appropriate sociocultural experience in language learning is essential.